High-flux ceramic ultrafiltration membrane
By introducing modified nanographene and aqueous polyurethane into the ceramic filter membrane to form a composite structure, the problems of low flux, poor retention and large brittleness of the ceramic filter membrane are solved, and a high-throughput, high separation efficiency and durability of ceramic ultrafiltration membrane are achieved.
Patent Information
- Application Number
- CN202510195454.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-18
AI Technical Summary
The low permeability, poor retention capacity and high ceramic brittleness of ceramic membranes have led to technical challenges in the treatment of oil-containing wastewater and dye wastewater.
By introducing modified nanographene and aqueous polyurethane into the ceramic base film, a composite structure is formed, the flux and separation efficiency of the ceramic filter membrane are improved, and the mechanical properties of the polyurethane are enhanced by crosslinking agents, reducing the brittleness of the ceramic membrane.
It significantly improves the flux, separation efficiency and durability of the ceramic filter membrane, reduces brittleness and extends service life.
Smart Images

Figure BDA0005281360250000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic membrane processing, and in particular to a high-flux ceramic ultrafiltration membrane. Background Art
[0002] Ceramic filter membranes are widely used in the treatment of oily wastewater, dye wastewater, heavy metal wastewater and other fields due to their high thermal stability, corrosion resistance and long service life. They can effectively remove organic pollutants, heavy metal ions and suspended solids, and recover valuable substances. At the same time, they also play an important role in food processing, such as the clarification and concentration of juice, wine, milk, tea, coffee, etc. They can remove impurities while retaining the flavor and nutrients of food, separate proteins, remove bacteria, enzymes and colloids, and improve food safety.
[0003] However, ceramic materials themselves are brittle and are prone to microcracks during the preparation process, or the membrane may rupture due to temperature changes or mechanical stress during use. Compared with polymer membranes, ceramic membranes have lower flux and require a larger membrane area to achieve the same treatment effect. In addition, in the preparation process of ceramic membranes, polymers are usually introduced into the surface and pore size of ceramic membranes by impregnation, so that the strong interaction between the polymer layer and the ceramic support leads to a decrease in the pore size and porosity of the membrane, thereby improving the performance of the ceramic membrane in oil-water separation. This method of introducing polymers can easily cause the membrane-forming material to penetrate into the large pores of the support, thereby greatly reducing the flux of the membrane. Therefore, ceramic filtration membranes still face certain technical challenges in improving flux, enhancing retention rate capabilities and avoiding brittleness. Summary of the invention
[0004] The object of the present invention is to provide a high-flux ceramic ultrafiltration membrane, which is used to solve the technical problems of low permeation flux, poor interception rate and high ceramic brittleness of the ceramic filtration membrane in the prior art.
[0005] The purpose of the present invention can be achieved by the following technical solution: a high-flux ceramic ultrafiltration membrane, wherein the high-flux ceramic ultrafiltration membrane is processed by the following steps:
[0006] S1, adding 2wt% polyvinyl alcohol solution, α-Al2O3 powder with a particle size of 25-30μm, corn starch, and polyacrylic acid into a reaction kettle and stirring, adding 5wt% acetic acid, adjusting the system pH to 5, and obtaining alumina slurry;
[0007] S2, adding 50wt% alumina slurry and modified nanographene into a high-speed shear mixer, and post-processing to obtain a ceramic-based support membrane;
[0008] S3, pouring the casting liquid into the ceramic support membrane, scraping and finishing, and post-processing to obtain a ceramic ultrafiltration membrane.
[0009] The synthetic reaction mechanism of the ceramic-based support membrane is:
[0010] Tetraethoxysilane undergoes a hydrolysis reaction to release ethanol and generate silanol groups, which undergo a dehydration condensation reaction with (-AlOH) and (-AlOOH) on the surface of aluminum oxide to form Al-O-Si bonds and hydrogen bonds. The hydroxyl groups on the surface of aluminum oxide form a hydrogen bond network with (Si-OH, Si-O-Si, -OH) on the surface of modified graphene oxide.
[0011] Furthermore, in step S1, the dosage ratio of 2 wt% polyvinyl alcohol solution, α-Al2O3 powder with a particle size of 25-30 μm, corn starch, and polyacrylic acid is: 9000-10000 mL: 180-200 g: 45-55 g: 2-4 g, stirring for 1-2 h, and the reaction temperature is 30-40°C.
[0012] Furthermore, in step S2, the amount ratio of 50wt% alumina slurry and modified nano-graphene is 100-200ml:1-2g, shear stirring is carried out for 2-3h, heat preservation is carried out at 50-80℃, and the shear speed is 900r / min. The post-treatment includes: after the reaction is completed, it is placed in an 80℃ drying oven and dried to constant weight, sieving, granulating, and the granulated powder is placed in a mold with a mold diameter of 27.0mm and a thickness of 3.5mm. The support body is pressurized at 50MPa to obtain a support body, and the support body is placed in a high-temperature furnace at 700-1550℃ for calcination for 1-2h at a heating rate of 2℃ / min to obtain a ceramic-based support membrane.
[0013] Furthermore, in step S3, the amount ratio of the ceramic-based support membrane and the casting liquid is 180-200g:1000-1500mL, the modified polyurethane and dimethyl phthalate are mixed in a ratio of 2g:1000mL to obtain a casting liquid, the casting liquid is poured into the ceramic-based support membrane, and the film is scraped with a 200μm thick scraper. The post-treatment includes: quenching the scraped film in a water bath until the film is completely solidified, adding an ethanol solution with a concentration of 50% and soaking for 35-45h, the water bath quenching temperature is 15-25°C, and drying at room temperature to obtain a high-mobility ceramic diaphragm.
[0014] Furthermore, the modified nano-graphene is obtained by processing the following steps:
[0015] A1. Add graphene oxide, anhydrous ethanol and distilled water into an ultrasonic disperser, and disperse and stir for 30-40 minutes to obtain a graphene oxide suspension;
[0016] A2. Add graphene suspension, ammonia solution and tetraethoxysilane into a reaction kettle, stir for 22-24 hours, filter and post-treat to obtain modified nano-graphene.
[0017] The synthetic reaction mechanism of modified nanographene is:
[0018] Tetraethoxysilane undergoes a hydrolysis reaction, releasing ethanol and generating silanol groups, which react with the carboxyl, epoxy, and hydroxyl functional groups on the surface of graphene oxide to form covalent bonds (Si-OC), ester bonds, and hydrogen bonds. The silanol groups further undergo a condensation reaction to form silicon-oxygen-silicon. The silane molecules react with the oxygen functional groups of graphene oxide through (Si-O) bonds to form (Si-OC) bonds.
[0019] Furthermore, in step A1, the amount ratio of graphene oxide, anhydrous ethanol and distilled water is 0.3-0.5g:80-100mL:4-6mL, and the particle size of graphene oxide is 1-5μm; in step A2, the volume ratio of graphene suspension, ammonia solution and tetraethoxysilane is 90-100mL:6-8mL:3-5mL, and the post-treatment includes: adding anhydrous ethanol for washing after filtration, filtration, and drying the filter cake in a vacuum drying oven at a temperature of 50-60°C to constant weight to obtain modified nano-graphene.
[0020] Furthermore, the modified polyurethane preparation method is:
[0021] B1. Add acetonitrile, acryloyl chloride and 1,4-butanediamine to a -20°C ice bath agitator, react at low temperature for 1-2 hours under a nitrogen atmosphere, and post-processing includes: reacting in a 30°C oil bath for 2-4 hours, filtering with suction, washing with acetonitrile, filtering with suction, drying in a 70°C vacuum oven to constant weight, placing the product in a -28°C 80wt% methanol / water mixture for recrystallization, filtering with suction, and drying in a 80°C vacuum oven to constant weight to obtain a cross-linking agent;
[0022] B2. Add waterborne polyurethane, crosslinking agent and 0.01 g / mL ammonium persulfate aqueous solution into a reaction kettle and stir, and then perform post-treatment to obtain modified polyurethane.
[0023] The synthetic reaction mechanism of modified polyurethane is:
[0024] The crosslinking agent contains two acrylamide groups, so the amino groups in the crosslinking agent undergo nucleophilic addition reaction with the epoxy groups in the waterborne polyurethane to form an amino-ethoxymethyl ether structure.
[0025] Furthermore, the volume ratio of acetonitrile, acryloyl chloride and 1,4-butanediamine is 6-8:12-14:10-12, the amount ratio of waterborne polyurethane, crosslinking agent and 0.01g / mL ammonium persulfate aqueous solution is 100-200g:1-2g:0.01-0.05mL, and the post-treatment includes: after the reaction is completed, removing ethanol under reduced pressure, placing in a vacuum oven at 70°C and drying to constant weight to obtain modified polyurethane, and the preparation method of waterborne polyurethane is: adding polyethylene glycol, polycarbonate diol, isophorone diisocyanate, diphenylmethane diisocyanate and toluene into a reactor and stirring, the reactor temperature is 100-120°C, and the reaction is kept warm for 2-4h, the reactor temperature is reduced by 50-80°C, and the reaction is kept warm for 1-2h, triethylamine is added to adjust the system to neutral, and the waterborne polyurethane is obtained by post-treatment.
[0026] Furthermore, the dosage ratio of polyethylene glycol, polycarbonate diol, isophorone diisocyanate, diphenylmethane diisocyanate and toluene is 20-30g:10-20g:30-50mL:5-10g:200-300mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to 80-90°C, and the low-boiling point molecules are evaporated under reduced pressure to obtain water-based polyurethane.
[0027] The present invention has the following beneficial effects:
[0028] 1. The nano-scale silica particles formed by tetraethoxysilane will increase the roughness of the graphene oxide surface and form micropores or irregular structures introduced on the alumina ceramic membrane, which is beneficial to capture pollutants during the filtration process. The silanol groups on the surface of the modified graphene oxide react with the surface active groups (Al-OH, -AlOOH) of the alumina ceramic membrane to form Al-O-Si bonds, and at the same time, they are tightly combined with the ceramic membrane through physical adsorption, mechanical interlocking, etc. This composite structure significantly improves the flux, separation efficiency and durability of the ceramic filtration membrane.
[0029] 2. The cross-linking agent containing double bonds prepared by the present invention is introduced into the molecular chain of waterborne polyurethane to form a double cross-linking network. At the same time, the amide bonds in the cross-linking agent can form hydrogen bonds with the main chain of the polyurethane, thereby improving the mechanical properties and water resistance of the polyurethane. In addition, the amino groups in the modified polyurethane undergo condensation reactions with the (Si-OH) and (Al-OH) bonds on the surface of modified alumina, and the formed chemical bonds form a flexible layer on the surface or in the pores of the alumina ceramic-based membrane, increasing the elasticity and impact resistance of the membrane, thereby reducing brittleness.
[0030] 3. The hydrogen bonds formed between the hydroxyl groups in the modified alumina and the hydroxyl groups and carboxyl groups in the modified polyurethane, as well as the aromatic ring structure on the graphene oxide can interact with the aromatic ring structure in the polyurethane through π-π stacking, further enhancing the interfacial bonding force between the two. These interactions not only enhance the structural stability of the membrane, avoid the increase in brittleness caused by interface detachment between the ceramic-based membrane and the outer layer material, but also reduce the propagation of microcracks in the membrane, and reduce the risk of membrane breakage under external impact or stretching. Therefore, by introducing polyurethane modification into the modification method of alumina-based ceramic membranes, the brittleness and durability of the ceramic filter membrane can be effectively improved, thereby extending its service life. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] This embodiment provides a method for preparing a high-flux ceramic ultrafiltration membrane, comprising the following steps:
[0034] S1. Preparation of alumina slurry
[0035] Weigh: 3000 mL of 2wt% polyvinyl alcohol solution, 180 g of α-Al2O3 powder with a particle size of 25-30 μm, 45 g of corn starch, and 2 g of polyacrylic acid, add into a reaction kettle and stir for 1 hour, set the temperature to 30°C, add 5wt% acetic acid, adjust the system pH to 5, and obtain alumina slurry.
[0036] S2. Preparation of graphene oxide suspension
[0037] Weigh 0.3 g of graphene oxide with a particle size of 1-5 μm, 80 mL of anhydrous ethanol, and 4 mL of distilled water, add them into an ultrasonic disperser, disperse and stir for 30 minutes, and obtain a graphene oxide suspension.
[0038] S3. Preparation of modified nanographene
[0039] Weigh: 90 mL of graphene suspension, 6 mL of ammonia solution, and 3 mL of tetraethoxysilane, add into the reactor, stir for 22 h, after the reaction is completed, filter, add anhydrous ethanol for washing, filter, and place the filter cake in a vacuum drying oven at 50° C. and dry to constant weight to obtain modified nanographene.
[0040] S4. Preparation of ceramic-based support membrane
[0041] Weigh: 100 ml of 50wt% alumina slurry and 1 g of modified nano-graphene, add into a high-speed shear mixer, shear and stir for 2 hours, keep warm at 50°C, and shear speed at 900r / min. After the reaction is completed, place in an 80°C drying oven and dry to constant weight, sieve, and granulate. Put the granulated powder into a mold with a mold diameter of 27.0 mm and a thickness of 3.5 mm, and pressurize at 50 MPa to obtain a support body. Place the support body in a high-temperature furnace and bake for 1 hour. The baking temperature is 700°C and the heating rate is 2°C / min to obtain a ceramic-based support membrane.
[0042] S5. Preparation of cross-linking agent
[0043] Weigh: add 6 mL of acetonitrile, 12 mL of acryloyl chloride, and 10 mL of 1,4-butanediamine into a -20°C ice bath stirrer, react at low temperature for 1 h under a nitrogen atmosphere, then react in an oil bath at 30°C for 2 h, filter, wash with acetonitrile, filter, and dry in a 70°C vacuum oven to constant weight. Recrystallize the product in a -28°C 80wt% methanol / water mixture, filter, and dry in a 80°C vacuum oven to constant weight to obtain a cross-linking agent.
[0044] S6. Preparation of waterborne polyurethane
[0045] Weigh: 20 g of polyethylene glycol, 10 g of polycarbonate diol, 30 mL of isophorone diisocyanate, 5 g of diphenylmethane diisocyanate, and 200 mL of toluene, add into a reactor and stir. The temperature of the reactor is 100°C, and the reaction is kept warm for 2 hours. The temperature of the reactor is reduced by 50°C, and the reaction is kept warm for 1 hour. Triethylamine is added to adjust the system to neutral. After the reaction is completed, the temperature of the reactor is increased to 85°C, and the low-boiling point molecules are evaporated under reduced pressure to obtain water-based polyurethane.
[0046] S7. Preparation of modified polyurethane
[0047] Weigh: 100 g of waterborne polyurethane, 1 g of cross-linking agent, and 0.01 mL of 0.01 g / mL ammonium persulfate aqueous solution, add into a reactor and stir. After the reaction is completed, remove ethanol under reduced pressure, place in a vacuum oven at 70° C. and dry to constant weight to obtain modified polyurethane.
[0048] S8. Preparation of ceramic ultrafiltration membrane
[0049] The modified polyurethane and dimethyl phthalate were mixed uniformly at a ratio of 2 g:1000 mL to obtain a casting solution;
[0050] Weigh: 180 g of ceramic-based support membrane and 1000 mL of casting liquid, pour the casting liquid into the ceramic-based support membrane, scrape the membrane with a 200 μm thick scraper, quench the scraped membrane in a water bath until the membrane is completely solidified, add 50% ethanol solution and soak for 35 hours. The water bath quenching temperature is 15°C, and dry at room temperature to obtain a high-mobility ceramic diaphragm.
[0051] Example 2
[0052] This embodiment provides a method for preparing a high-flux ceramic ultrafiltration membrane, comprising the following steps:
[0053] S1. Preparation of alumina slurry
[0054] Weigh: 4000 mL of 2wt% polyvinyl alcohol solution, 190 g of α-Al2O3 powder with a particle size of 25-30 μm, 50 g of corn starch, and 3 g of polyacrylic acid, add into a reactor and stir for 1.5 h, set the temperature to 35°C, add 5wt% acetic acid, adjust the system pH to 5, and obtain alumina slurry.
[0055] S2. Preparation of graphene oxide suspension
[0056] Weigh 0.4 g of graphene oxide with a particle size of 1-5 μm, 90 mL of anhydrous ethanol, and 5 mL of distilled water into an ultrasonic disperser, and disperse and stir for 35 minutes to obtain a graphene oxide suspension.
[0057] S3. Preparation of modified nanographene
[0058] Weigh: 95 mL of graphene suspension, 7 mL of ammonia solution, and 4 mL of tetraethoxysilane, add into the reaction kettle, stir for 23 h, after the reaction is completed, filter, add anhydrous ethanol for washing, filter, and place the filter cake in a vacuum drying oven at 55 ° C to dry to constant weight to obtain modified nano-graphene.
[0059] S4. Preparation of ceramic-based support membrane
[0060] Weigh: 150 ml of 50wt% alumina slurry and 1.5 g of modified nano-graphene, add into a high-speed shear mixer, shear and stir for 2.5 hours, keep warm at 70°C, shear speed 900r / min, after the reaction is completed, place in an 80°C drying oven to constant weight, sieve, granulate, put the granulated powder into a mold with a mold diameter of 27.0 mm and a thickness of 3.5 mm, pressurize at 50 MPa to obtain a support body, place the support body in a high-temperature furnace for baking for 1.5 hours, the baking temperature is 1000°C, and the heating rate is 2°C / min to obtain a ceramic-based support membrane.
[0061] S5. Preparation of cross-linking agent
[0062] Weigh: add 7 mL of acetonitrile, 13 mL of acryloyl chloride, and 11 mL of 1,4-butanediamine into a -20°C ice bath stirrer, react at low temperature for 1.5 h under a nitrogen atmosphere, then react in an oil bath at 30°C for 3 h, filter, wash with acetonitrile, filter, and dry in a 70°C vacuum oven to constant weight. Recrystallize the product in a -28°C 80wt% methanol / water mixture, filter, and dry in a 80°C vacuum oven to constant weight to obtain a cross-linking agent.
[0063] S6. Preparation of waterborne polyurethane
[0064] Weigh: 25 g of polyethylene glycol, 15 g of polycarbonate diol, 35 mL of isophorone diisocyanate, 8 g of diphenylmethane diisocyanate, and 250 mL of toluene, add into a reactor and stir, the reactor temperature is 150°C, keep warm for reaction for 3 hours, reduce the reactor temperature by 60°C, keep warm for reaction for 1.5 hours, add triethylamine to adjust the system to neutral, after the reaction is completed, raise the reactor temperature to 80-90°C, and evaporate under reduced pressure to remove low-boiling point molecules to obtain waterborne polyurethane.
[0065] S7. Preparation of modified polyurethane
[0066] Weigh: 150 g of waterborne polyurethane, 1.5 g of cross-linking agent, and 0.03 mL of 0.01 g / mL ammonium persulfate aqueous solution, add into a reactor and stir. After the reaction is completed, remove ethanol under reduced pressure, place in a vacuum oven at 70° C. and dry to constant weight to obtain modified polyurethane.
[0067] S8. Preparation of ceramic ultrafiltration membrane
[0068] The modified polyurethane and dimethyl phthalate were mixed uniformly at a ratio of 2 g:1000 mL to obtain a casting solution;
[0069] Weigh: 190 g of ceramic-based support membrane and 1300 mL of casting liquid, pour the casting liquid into the ceramic-based support membrane, scrape the membrane with a 200 μm thick scraper, quench the scraped membrane in a water bath until the membrane is completely solidified, add 50% ethanol solution and soak for 40 hours. The water bath quenching temperature is 20°C, and dry at room temperature to obtain a high-mobility ceramic diaphragm.
[0070] Example 3
[0071] This embodiment provides a method for preparing a high-flux ceramic ultrafiltration membrane, comprising the following steps:
[0072] S1. Preparation of alumina slurry
[0073] Weigh: 5000 mL of 2wt% polyvinyl alcohol solution, 200 g of α-Al2O3 powder with a particle size of 30 μm, 55 g of corn starch, and 4 g of polyacrylic acid, add into a reactor and stir for 2 h. Set the temperature to 40°C, add 5wt% acetic acid, adjust the system pH to 5, and obtain alumina slurry.
[0074] S2. Preparation of graphene oxide suspension
[0075] Weigh 0.5 g of graphene oxide with a particle size of 1-5 μm, 100 mL of anhydrous ethanol, and 6 mL of distilled water, add them into an ultrasonic disperser, disperse and stir for 40 minutes, and obtain a graphene oxide suspension.
[0076] S3. Preparation of modified nanographene
[0077] Weigh: 100 mL of graphene suspension, 8 mL of ammonia solution, and 5 mL of tetraethoxysilane, add into the reactor, stir for 24 h, after the reaction is completed, filter, add anhydrous ethanol for washing, filter, and place the filter cake in a vacuum drying oven at 60° C. to dry to constant weight to obtain modified nanographene.
[0078] S4. Preparation of ceramic-based support membrane
[0079] Weigh: 200 ml of 50wt% alumina slurry and 2 g of modified nano-graphene, add into a high-speed shear mixer, shear and stir for 3 hours, keep warm at 80°C, and shear speed at 900r / min. After the reaction is completed, place in an 80°C drying oven and dry to constant weight, sieve, and granulate. Put the granulated powder into a mold with a mold diameter of 27.0 mm and a thickness of 3.5 mm, and pressurize at 50 MPa to obtain a support body. Place the support body in a high-temperature furnace and calcine for 2 hours. The calcination temperature is 1550°C and the heating rate is 2°C / min to obtain a ceramic-based support membrane.
[0080] S5. Preparation of cross-linking agent
[0081] Weigh: add 8 mL of acetonitrile, 14 mL of acryloyl chloride, and 2 mL of 1,4-butanediamine into a -20°C ice bath stirrer, react at low temperature for 2 h under a nitrogen atmosphere, then react in a 30°C oil bath for 4 h, filter, wash with acetonitrile, filter, and dry in a 70°C vacuum oven to constant weight. Recrystallize the product in a -28°C 80wt% methanol / water mixture, filter, and dry in a 80°C vacuum oven to constant weight to obtain a cross-linking agent.
[0082] S6. Preparation of waterborne polyurethane
[0083] Weigh: 30g of polyethylene glycol, 20g of polycarbonate diol, 50mL of isophorone diisocyanate, 10g of diphenylmethane diisocyanate, and 300mL of toluene, add into a reactor and stir, the temperature of the reactor is 100-120°C, keep warm for 4h, reduce the temperature of the reactor to 80°C, keep warm for 2h, add triethylamine to adjust the system to neutral, after the reaction is completed, raise the temperature of the reactor to 80-90°C, and evaporate the low-boiling point molecules under reduced pressure to obtain waterborne polyurethane.
[0084] S7. Preparation of modified polyurethane
[0085] Weigh: 200 g of waterborne polyurethane, 2 g of cross-linking agent, and 0.05 mL of 0.01 g / mL ammonium persulfate aqueous solution, add into a reactor and stir. After the reaction is completed, remove ethanol under reduced pressure, place in a vacuum oven at 70° C. and dry to constant weight to obtain modified polyurethane.
[0086] S8. Preparation of ceramic ultrafiltration membrane
[0087] The modified polyurethane and dimethyl phthalate were mixed uniformly at a ratio of 2 g:1000 mL to obtain a casting solution;
[0088] Weigh: 200 g of ceramic-based support membrane and 1500 mL of casting liquid, pour the casting liquid into the ceramic-based support membrane, scrape the membrane with a 200 μm thick scraper, quench the scraped membrane in a water bath until the membrane is completely solidified, add 50% ethanol solution and soak for 45 hours. The water bath quenching temperature is 25°C, and dry at room temperature to obtain a high-mobility ceramic diaphragm.
[0089] Comparative Example 1
[0090] The difference between this comparative example and Example 3 is that in step S3, no modified nano-graphene is added.
[0091] Comparative Example 2
[0092] The difference between this comparative example and Example 3 is that in step S5, no cross-linking agent is added.
[0093] Comparative Example 3
[0094] The difference between this comparative example and Example 3 is that in step S7, no modified polyurethane is added.
[0095] Performance Test:
[0096] The performance of the high-flux ceramic ultrafiltration membranes prepared in Examples 1-3 and Comparative Examples 1-3 was tested, wherein the mechanical properties, separation performance, and flux of the ceramic filtration membranes were determined according to the standard HY / T 233-2018 "Ultrafiltration Membrane Performance Test Method Part 1: General Principles" to determine the pure water flux, retention rate, breaking strength, and elongation at break of the sample. The specific test results are shown in Table 1:
[0097] Table 1-Performance test data of the sample
[0098]
[0099] Data Analysis:
[0100] It can be seen from the relevant data in Table 1 that, compared with the comparative example, the ceramic ultrafiltration membrane provided by the present invention, which is obtained by introducing special wettable nanomaterials and modified polyurethane into the surface and pore size of the alumina base membrane by an impregnation method, significantly improves the flux, retention rate, breaking strength and breaking elongation of the filtration membrane, so that the filtration membrane improves the separation performance and mechanical properties of the modified membrane while retaining the original membrane pore size.
[0101] Compared with Examples 1-3, the pure water flux of Comparative Example 1 is decreased, indicating that the silanol groups on the surface of the modified graphene oxide react with the surface active groups (Al-OH, -AlOOH) of the alumina ceramic membrane to form Al-O-Si bonds, and at the same time, they are tightly combined with the ceramic membrane through physical adsorption, mechanical interlocking, etc. This composite structure significantly improves the flux and separation efficiency of the ceramic filtration membrane.
[0102] Compared with Examples 1-3, the breaking strength and elongation at break of Comparative Example 2 are decreased, indicating that the amide bonds in the cross-linking agent can form hydrogen bonds with the main chain of the polyurethane, thereby improving the mechanical properties and water resistance of the polyurethane.
[0103] Compared with Examples 1-3, the breaking strength and elongation at break of Comparative Example 3 are significantly reduced, indicating that the hydrogen bonds formed between the hydroxyl groups in the modified alumina and the hydroxyl groups and carboxyl groups in the modified polyurethane, and the aromatic ring structure on the graphene oxide can interact with the aromatic ring structure in the polyurethane through π-π stacking, further enhancing the interfacial bonding force between the two. These interactions not only enhance the structural stability of the membrane, avoid the increase in brittleness caused by interface detachment between the ceramic-based membrane and the outer layer material, but also reduce the propagation of microcracks in the membrane, reducing the risk of membrane breakage under external impact or stretching.
[0104] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high-flux ceramic ultrafiltration membrane, characterized in that: The high flux ceramic ultrafiltration membrane is processed by the following steps: S1, adding polyvinyl alcohol solution, α-Al2O3 powder, corn starch and polyacrylic acid into a reaction kettle and stirring, adding acetic acid, adjusting the pH value of the system to 5, and obtaining alumina slurry; S2, adding alumina slurry and modified nano-graphene into a high-speed shear mixer, and post-processing to obtain a ceramic-based support membrane; S3, pouring the casting liquid into the ceramic support membrane, scraping and finishing, and post-processing to obtain a ceramic ultrafiltration membrane.
2. A high flux ceramic ultrafiltration membrane according to claim 1, characterized in that: In step S1, the amount ratio of polyvinyl alcohol solution, α-Al2O3 powder, corn starch and polyacrylic acid is: 3000-5000mL: 180-200g: 45-55g: 2-4g, the mass fraction of polyvinyl alcohol solution is 2wt%, the particle size of α-Al2O3 powder is 25-30μm, stirring is 1-2h, and the reaction temperature is 30-40℃.
3. A high flux ceramic ultrafiltration membrane according to claim 1, characterized in that: In step S2, the ratio of alumina slurry to modified nanographene is 100-200 ml: 1-2 g, the mass fraction of alumina slurry is 50 wt%, shear stirring is performed for 2-3 h, the temperature is kept at 50-80° C., the shear speed is 900 r / min, and post-treatment is performed to obtain a ceramic-based support membrane.
4. A high flux ceramic ultrafiltration membrane according to claim 1, characterized in that: In step S3, the ratio of the amount of ceramic-based support membrane and the casting liquid is 180-200g:1000-1500mL, the modified polyurethane and dimethyl phthalate are mixed evenly at a ratio of 2g:1000mL to obtain the casting liquid, the casting liquid is poured into the ceramic-based support membrane, and the membrane is scraped with a 200μm thick scraper, and the ceramic ultrafiltration membrane is obtained by post-processing.
5. A high flux ceramic ultrafiltration membrane according to claim 1, characterized in that: The modified nano-graphene is obtained by processing the following steps: A1. Add graphene oxide, anhydrous ethanol and distilled water into an ultrasonic disperser, and disperse and stir for 30-40 minutes to obtain a graphene oxide suspension; A2. Add graphene suspension, ammonia solution and tetraethoxysilane into a reaction kettle, stir for 22-24 hours, filter and post-treat to obtain modified nano-graphene.
6. A high flux ceramic ultrafiltration membrane according to claim 5, characterized in that: In step A1, the amount ratio of graphene oxide, anhydrous ethanol and distilled water is 0.3-0.5g:80-100mL:4-6mL, and the particle size of graphene oxide is 1-5μm; in step A2, the volume ratio of graphene suspension, ammonia solution and tetraethoxysilane is 90-100mL:6-8mL:3-5mL, and modified nano-graphene is obtained by post-treatment.
7. A high flux ceramic ultrafiltration membrane according to claim 4, characterized in that: The modified polyurethane preparation method is: B1. Add acetonitrile, acryloyl chloride and 1,4-butanediamine into a -20°C ice bath stirrer, react at low temperature for 1-2 hours under a nitrogen atmosphere, and post-treat to obtain a cross-linking agent; B2. Add waterborne polyurethane, crosslinking agent and 0.01 g / mL ammonium persulfate aqueous solution into a reaction kettle and stir, and then perform post-treatment to obtain modified polyurethane.
8. A high flux ceramic ultrafiltration membrane according to claim 7, characterized in that: The volume ratio of acetonitrile, acryloyl chloride and 1,4-butanediamine is 6-8:12-14:10-12, the dosage ratio of waterborne polyurethane, crosslinking agent and 0.01g / mL ammonium persulfate aqueous solution is 100-200g:1-2g:0.01-0.05mL, and modified polyurethane is obtained by post-treatment. The preparation method of waterborne polyurethane is as follows: polyethylene glycol, polycarbonate diol, isophorone diisocyanate, diphenylmethane diisocyanate and toluene are added into a reaction kettle and stirred, the temperature of the reaction kettle is 100-120°C, and the reaction is kept warm for 2-4h, the temperature of the reaction kettle is reduced by 50-80°C, and the reaction is kept warm for 1-2h, triethylamine is added to adjust the system to neutral, and waterborne polyurethane is obtained by post-treatment.
9. A high flux ceramic ultrafiltration membrane according to claim 8, characterized in that: The dosage ratio of polyethylene glycol, polycarbonate diol, isophorone diisocyanate, diphenylmethane diisocyanate and toluene is 20-30g:10-20g:30-50mL:5-10g:200-300mL, and waterborne polyurethane is obtained by post-treatment.